Beer-gut microbiome alliance: a discussion of beer-mediated immunomodulation via the gut microbiome - Zhang, Silu; Jin, Shuo; Zhang, Cui; Hu, Shumin; Li, Huajun (Frontiers in Nutrition, 2023)
As a long-established fermented beverage, beer is rich in many essential amino acids, vitamins, trace elements, and bioactive substances that are involved in the regulation of many human physiological functions. The polyphenols in the malt and hops of beer are also important active compounds that interact in both directions with the gut microbiome. This review summarizes the mechanisms by which polyphenols, fiber, and other beneficial components of beer are fermentatively broken down by the intestinal microbiome to initiate the mucosal immune barrier and thus participate in immune regulation. Beer degradation products have anti-inflammatory, anticoagulant, antioxidant, and glucolipid metabolism-modulating potential. We have categorized and summarized reported data on changes in disease indicators and in vivo gut microbiota abundance following alcoholic and non-alcoholic beer consumption. The positive effects of bioactive substances in beer in cancer prevention, reduction of cardiovascular events, and modulation of metabolic syndrome make it one of the candidates for microecological modulators.